The library dragon - Deedy, Carmen Agra. frey50; White, Michael P. (Atlanta : Peachtree, 1994)
Miss Lotta Scales is a dragon who believes her job is to protect the school's library books from the children, but when she finally realizes that books are meant to be read, the dragon turns into Miss Lotty, librarian and storyteller.
71585
Keywords: Librarians -- Fiction; Dragons -- Fiction; Libraries -- Fiction; Books and reading -- Fiction; Schools -- Fiction